Calcium in Photosynthetic Restoration and Growth of Annona emarginata after Mechanical Damage - Campos, Felipe Girotto [UNESP]; Barzotto, Gustavo Ribeiro [UNESP]; Pagassini, Jonas Akenaton Venturineli [UNESP]; Sousa, Marilia Caixeta [UNESP]; Ferreira, Gisela [UNESP]; Boaro, Carmen Sílvia Fernandes [UNESP] (MDPI, 2022)
Calcium, an essential element with structural function in the cell wall and plasma membrane, in addition to being a secondary messenger, is responsible for the regulation of physiological processes in plant development and responses to biotic and abiotic stresses. This study investigated the effects of calcium variation on photosynthetic performance, growth, and enzymatic antioxidant defense system in A. emarginata subjected to mechanical damage. The experimental design was in 6 × 5 factorial randomized blocks. A. emarginata plants were submitted to the six treatments: plants grown in solution with 0 mM Ca2+ without mechanical damage, 0 mM Ca2+ with mechanical damage, 2 mM Ca2+ without mechanical damage, 2 mM Ca2+ with mechanical damage, 4 mM Ca2+ without mechanical damage, and 4 mM Ca2+ with mechanical damage, as well as five evaluation periods at 0, 15, 30, 60, and 90 days after mechanical damage. The fluorescence of chlorophyll a, gas exchange, total dry mass, quantitative growth, and lipid peroxidation was studied. It is concluded that the A. emarginata plants showed better performance in restoration after mechanical damage in the presence of Ca2+ and was more sensitive in the absence of the mineral. Cultivation of the species with 2 mM Ca2+ in complete nutrient solution was sufficient to guarantee the efficiency of the enzymatic antioxidant defense system, and photosynthetic restoration of plants subjected to mechanical damage.
Keywords: antioxidant enzymes; calcium metabolism; chlorophyll a fluorescence; gas exchange; hydrogen peroxide; plant physiology